Pool Chemicals and Personal Safety - Fred Fishel (EDIS)
Pool chemicals are among the most common household substances and are used to protect health in recreational waters. Pool chemicals containing chlorine safeguard against recreational-water illnesses caused by disease-causing pathogens, such as the diarrhea-causing Cryptosporidium. They also enhance disinfection by regulating water pH. But even though these materials are regularly handled by homeowners, most don’t ever realize that they are handling pesticides. This 3-page fact sheet was written by Fred Fishel, and published by the UF Department of Agronomy, September 2014.